Reação de redução de compostos nitrogenados: de aspectos fundamentais em monocristais de Pt à utilização de nanopartículas bimetálicas - Silva, Kaline Nascimento da (Universidade Federal de São Carlos, 2022)
Because of the high consumption of nitrogen-based compounds by both industry and agriculture, there is an imbalance in nitrogen cycle and the nitrate and nitrite reduction reaction can be a solution. These processes are formed by several intermediates which depend on both applied potential and the catalysts. Thus, it is crucial the understanding of the role of active sites, shape, and composition of nanocatalysts, and optical properties to increase the reaction selectivity. The main goal of this work is to compare different catalysts for nitrate and nitrite reduction reaction (NO3RR and NO2RR) on single crystals (Pt(111) and Pt(110)), shape-controlled Pt nanoparticles (cube (c), cuboctahedron (co) and, octahedron (oct)) and also bimetallic nanoparticles such as Pt@Cu and Au(100-x)PdX in acidic media. The experiments on the Pt single crystals revealed that NO3RR exhibit lower activity on {111} surface than {110} surface; yielding apparent reaction orders of 0.13 and 0,0 at 0.15 V on Pt(110) and Pt(111), respectively. Besides that, NO2RR showed multiple reduction processes and apparent reaction order of 0.65 and 0.60 on Pt(111) and Pt(110) respectively. Using cyanide-modified Pt(111) electrode, Pt(111)-CN, while NO2RR is partially inhibited, NO3RR is totally inhibited, thus the rate determining step for this reaction depends on fcc-hollow sites for tridentate nitrate adsorption, or the hydrogen adsorption near the adsorbed nitrate. Using shape-controlled nanoparticles, 4 nitrophenol hydrogenation relies of crystalline plane exposed. Furthermore, the capping agent used (polyvinylpyrrolidone – PVP) has a platinum interaction in this following order: Ptc < Ptco < Ptoct. Residual PVP affects the current densities for reactions studied. Nanoparticles capping agent-free exhibited lower activities for NO3RR than NO2RR. After copper deposition on Pt nanoparticles, (Pt@Cu), there was an activity enhancement between the bimetallic catalysts for RRNO3, as follow: Ptco < Ptc < Ptoct and for RRNO2: Ptoct < Ptc < Ptco. Lastly, the AuPd catalysts with light showed an increase of 16, 71 and 124% in current densities at 0.1 V for RRNO2 in the systems Au95Pd5, Au97,5Pd2,5 e Au99,5Pd0,5 respectively. These results demonstrate the adsorbates importance for selectivity during RRNO3, and the synergic effect between the metals with or without light.
Nitrogen-based compounds reduction reactions: from fundamental studies on pt single crystals to bimetallic nanoparticles
Keywords: Eletrocatálise; Reação de redução de compostos nitrogenados; Pt(hkl); Nanopartículas de Pt com morfologia controlada; Nanopartículas bimetálicas; CIENCIAS EXATAS E DA TERRA::QUIMICA::FISICO-QUIMICA